Spesies Diversity and Abudance of Nudibranchia in Tulamben Waters, Bali - Marchel Marchel; Felicia Zahida; Ign. Pramana Yuda (Masyarakat Moluska Indonesia, 2021)
Nudibranchia is the largest order of Opistobranchia which is known to have about 3,000 species. Nudibranchia is a popular macro photography object among divers. Although Tulamben Waters, Bali is one of popular destination for macrobiota’s habitat, but research on marine biota, especially nudibranchia in these waters is still very rare. This study uses two methods, which is direct observation to reveal diversity and species number, belt transect methods to estimate density or abundance per sampling area using diving techniques . A transect line of 50 m at each point of observation site was used to evaluate abundance. This study wants to see the level of diversity, mapping various species and abundance of nudibranchia. For biodiversity, 31 species from 15 families are found, Chromodoridae, Dorididae, Elysiidae, Facelinidae, Flabellinidae, Goniodorididae, Halgerdidae, Hexabranchidae, Phyllidiidae Polyceridae, Hydatinidae, Costasiellidae, Elysiidae and Limapontiidae. Whereas the transect method found 12 species from 6 families, Chromodoridae, Facelinidae, Phyllidiidae Aglajidae, Costasiellidae, and Elysiidae. With a diversity index of 2.27 and the highest level of abundance found in Pteraeolidia ianthina species with a relative abundance of 0.19%.